(untitled) (The Review of Diabetic Studies, 2025)
This article provides a comprehensive analysis of health informatics applications in radiology and pharmacy sectors within Saudi Arabia’s healthcare system. The integration of information technology in these specialized medical fields has revolutionized healthcare delivery, yet it remains an evolving discipline in the Kingdom. Through examination of recent research and development initiatives, this study explores the features, contributions, applications, and limitations of health informatics in Saudi radiological and pharmaceutical services. Key findings indicate substantial progress in implementing electronic systems like PACS (Picture Archiving and Communication System) in radiology and Wasfaty for pharmacy services, while highlighting persistent challenges including workforce training gaps, interoperability issues, and regional disparities in technological adoption. The analysis reveals that despite significant governmental investment through Vision 2030 healthcare transformation initiatives, health informatics research and implementation in these specialized fields require further development to reach international standards. This work contributes to understanding the current landscape and future directions for health informatics in Saudi Arabia’s radiology and pharmacy domains, providing valuable insights for policymakers, healthcare administrators, and researchers.